The greatest prime function of real variable - Qarawani, Maher (Global Journal of Mathematical Analysis, 2015)
In this paper, we introduce a new function which we call the greatest prime function. In addition, we give an extension of the function to , and then use this definition to prove some inequalities and properties of this function. Some illustrative examples are given.